Internet-delivered therapist-assisted cognitive behavioral therapy for gambling disorder: a randomized controlled trial - Mide, Mikael; Mattiasson, Jessica; Norlin, David; Sehlin, Helena; Rasmusson, Josefine; Ljung, Sofia; Lindskog, Amanda; Petersson, Jonna; Saavedra, Fanny; Gordh, Anna Söderpalm (Frontiers in Psychiatry, 2023)
Objectives: Cognitive behavioral therapy (CBT) is the most promising treatment for Gambling Disorder (GD), but only 21% of those with problematic gambling seek treatment. CBT over the internet might be one way to reach a larger population. The aim of this study was to assess the effectiveness of internet-delivered CBT with therapist guidance compared to an active control treatment. Methods: Using a single-blinded design, 71 treatment seeking gamblers (18-75 years) diagnosed with GD were randomized to 8 weeks of internet-delivered CBT guided by telephone support, or 8 weeks of internet-delivered motivational enhancement paired with Motivational interviewing via telephone (IMI). The primary outcome was gambling symptoms measured at a first face-to-face assessment, baseline (treatment start), every two weeks, post-treatment and at 6-month follow-up. Gambling expenditures, time spent gambling, depression, anxiety, cognitive distortions, and quality-of-life were assessed as secondary outcomes. Analysis was performed on the Full Analysis Sample (n=60), with Intention-to-Treat sensitivity analyses (n=69). Results: In the CBT group, 80% stayed in treatment until the final week, compared to 67% in IMI. Post-treatment and at 6-month follow-up, no differences were found between CBT and IMI for any outcome measure. An exploratory analysis of the total sample (n=60) showed a significant effect of time during treatment on gambling symptoms (d, [95% CI]) 0.52, [-1.15, 2.02]) and all secondary outcomes except the gambling diary (depression, 0.89, [-1.07–2.65]; anxiety (0.69, [-1.20–2.38]); cognitive distortions (0.84, [-0.73–2.29]); quality of life (0.60, [-0.61–1.70]). Post-treatment there were no clinical gambling symptoms in either group. Some deterioration was seen between post-treatment and 6-month follow up on gambling symptoms (0.42, [-1.74–2.43]), depression (0.59, [-0.82–1.86]) and anxiety (0.30, [-0.99–1.48]). Additionally, it was observed that the largest reduction in gambling symptoms was between first assessment and baseline. Conclusion: Both treatments offered in this study were effective at reducing gambling symptoms. It is also possible that the process of change started before treatment, which gives promise to low-intensity interventions for GD. Additional research is needed as this approach could be both cost-effective and has the potential to reach more patients in need of treatment than is currently possible.